Dinosaurs Kids Can Draw - Legendre, Philippe (California Walter Foster, 1996)
Aimed at children aged between four and seven, this book teaches children to draw dinosaurs by transforming simple circles, squares and triangles into works of art. Each book in the series demonstrates how to draw nine pictures, and includes a letter to parents and tips for getting started.
D., 11/00
Keywords: Drawing -- Juvenile Fiction